Motivation to Work of Teacher Educators at Elementary Level of Teacher Education Institution - Savita Mishra; Vipin Sharma (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
Motivation to work denotes the directs aptitude and persistence of an individual’s behaviour in understanding the task. The objective of the study was to compare teachers’ motivation to work in the elementary level teacher education institutions due to the categorical variables like gender (male and female), teaching experience (more than 5 years teaching experience & less than 5 years teaching experience), type of management (Government and Self-financed) and locale (urban & rural). Descriptive survey method has been adopted in the present study. A sample of 100 teacher educators were randomly selected of which 50 teachers were from Government and 50 teachers were from self-financed institutions. The major variable is motivation to work and categorical variables are gender, teaching experience, types of management and locale. The finding revealed that there is no significant difference in motivation to work of teacher educators in relation to gender variation but significant difference in relation to teaching experience, type of management and locale variations.